Job Motivation and Organizational Commitment of Administration Officials under the Office of The Attorney General - Rungruang, Saran; Silphiphat, Kevalin (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The objectives of this research were 1) to study the job motivation towards the organization of administrative officials under the Office of the Attorney General, 2) to study the organizational commitment of administrative officials under the Office of the Attorney General, and 3) to study the relationship between job motivation and organizational commitment of administrative officials under the Office of the Attorney General. The population and the sample were 400 administrative officials of the Attorney General's Office. The research tool was a questionnaire. The statistics used to analyze the data were frequency, percentage, mean, standard deviation, and Pearson correlation coefficient. The results of the study were as follows: 1) the job motivation of administrative officials the average was at a high level, 2) the organizational commitment of administrative officials the average was at a high level, and 3) Job motivation on the motivation factors had a very low positive correlation with organizational commitment of administrative officials under the Office of the Attorney General, and job motivation on the hygiene factors had a moderate positive correlation with organizational commitment of administrative officials under the Office of the Attorney General at statistical significance at the .05 level.